2004
DOI: 10.1080/00288306.2004.9515035
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence age estimates of Pleistocene marine terrace and alluvial fan sediments associated with tectonic activity along coastal Otago, New Zealand

Abstract: Six luminescence age estimates have been obtained from raised beach sands and loess, and alluvial fan sediments in the outboard zone of the active Otago reverse fault province, coastal Otago, New Zealand. These age estimates constrain the timing of movement of the Akatore Fault and the Titri Fault System. Five of the samples were dated by optical dating of K-feldspar in the polymineral fine silt fraction; the remaining sample was dated using thermoluminescence (TL) emitted from quartz (fine sand fraction). Rai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 25 publications
1
30
0
Order By: Relevance
“…Although generally sparse, organic material is present as wood within the gravel-dominated deposits, and also occurs as peat in terrace cover deposits, and charcoal within tephras. Luminescence dating is being increasingly used in New Zealand to extend age control beyond the limits of radiocarbon dating, and has particularly been used to date loess (e.g., Berger et al, 1992Berger et al, , 2001Berger et al, , 2002Litchfield and Lian, 2004). The present study is the first to apply Optically Stimulated Luminescence (OSL) dating directly to fluvial deposits in the eastern North Island, although OSL ages of loess coverbeds have been used to estimate the minimum ages of river terrace deposits (Wang, 2001;Formento-Trigilio et al, 2003).…”
Section: Introductionmentioning
confidence: 96%
“…Although generally sparse, organic material is present as wood within the gravel-dominated deposits, and also occurs as peat in terrace cover deposits, and charcoal within tephras. Luminescence dating is being increasingly used in New Zealand to extend age control beyond the limits of radiocarbon dating, and has particularly been used to date loess (e.g., Berger et al, 1992Berger et al, , 2001Berger et al, , 2002Litchfield and Lian, 2004). The present study is the first to apply Optically Stimulated Luminescence (OSL) dating directly to fluvial deposits in the eastern North Island, although OSL ages of loess coverbeds have been used to estimate the minimum ages of river terrace deposits (Wang, 2001;Formento-Trigilio et al, 2003).…”
Section: Introductionmentioning
confidence: 96%
“…A comprehensive review by Jacobs (2008) compiles all these coastal studies and a review by Madsen and Murray (2009) summarizes the dating of young (<1000 years) coastal and aeolian sediments. So far, a limited number of studies have been published from coastal sites in New Zealand (Duller, 1996;Shulmeister et al 1999;ReesJones et al 2000;Nichol, 2002;Litchfield and Lian, 2004;Cooper and Kostro, 2006;Kennedy et al 2007) and these have focused mainly on Pleistocene deposits (older than 10,000 years). Only Shulmeister and Kirk (1996) and Nichol et al (2003) present chronologies on a millennial time-scale of Holocene (younger than 10,000 years) dune ridges.…”
Section: Introductionmentioning
confidence: 99%
“…The 65-km-long Akatore Fault has a maximum of c. 120 m of Quaternary uplift (Litchfield & Norris 2000). Detailed studies of the onshore section have identified two rupture events within the Holocene (Litchfield & Norris 2000;Litchfield & Lian 2004). The youngest rupture is well constrained by 14 radiocarbon ages at AD 800Á950 (Litchfield & Norris 2000), although McFadgen (2007) has reinterpreted the constraining dates and extended the possible age to lie between AD 900 and 1450.…”
Section: Late Holocene Faults Of Coastal Otagomentioning
confidence: 99%